MODERN EPIDEMIOLOGICAL ASPECTS AND EARLY DETECTION OF PARKINSON’S DISEASE - Z. A. Goncharova; I. V. Chernikova; E. A. Rabadanova; H. I. Hadzieva (Медицинский вестник Юга России, 2014)
The necessity of study of Parkinson’s disease (PD) is caused by the increasing number of elderly people in the modern population in developed countries, and, as a result, growing of prevalence number.In clinical practice high percentage of hypodiagnosis of PD. Diagnostic of PD – particularly in its early stages, knowledge of the diagnostic criteria, modern neurovisualisation methods, allowed to differentiate PD with parkinsonism and to make accurate diagnose and to administrate correct treatment.